Neural Basis of the Emotional Conflict Processing in Major Depression: ERPs and Source Localization Analysis on the N450 and P300 Components - Zhu, Jing; Li, Jianxiu; Li, Xiaowei; Rao, Juan; Hao, Yanrong; Ding, Zhijie; Wang, Gangping (Frontiers in Human Neuroscience, 2018)
Objects: Effective psychological function requires that cognition is not affected by task-irrelevant emotional stimuli in emotional conflict. Depression is mainly characterized as an emotional disorder. The object of this study is to reveal the behavioural and electrophysiological signature of emotional conflict processing in major depressive disorder (MDD) using ERPs and sLORETA analysis. Method: We used a face-word Stroop task involving emotional faces while recording EEG (electroencephalography) in 20 patients with MDD and 20 healthy controls (HCs). And then event-related potentials (ERPs) were extracted and the corresponding brain sources were reconstructed using standardized low-resolution brain electromagnetic tomography (sLORETA). Results: Behaviorally, subjects with MDDs manifested significantly increased Stroop effect when examining the RT difference between happy incongruent trials and happy congruent trials, compared with HC subjects. ERP results exhibited that MDDs were characterized by attenuated difference between P300 amplitude to sad congruent stimuli and sad incongruent stimuli, as electrophysiological evidence of impaired conflict processing in subjects with MDD. The sLORETA results showed that MDD patients had higher current density in rostral anterior cingulate cortex (rostral ACC) within N450 time window in response to happy incongruent trials than happy congruent stimuli. Moreover, HC subjects had stronger activity in right inferior frontal gyrus (rIFG) region in response to incongruent stimuli than congruent stimuli, revealing successful inhibition of emotional distraction in HCs, which was absent in MDDs. Conclusions: Our results indicated that rostral ACC was implicated in the processing of negative emotional distraction in MDDs, as well as impaired inhibition of task-irrelevant emotional stimuli, relative to HCs. This work furnishes novel behavioral and neurophysiological evidence that are closely related to emotional conflict among MDD patients.